2022
DOI: 10.1097/tld.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Motivation as a Predictor of Aphasia Treatment Outcomes

Abstract: Motivation is a complex phenomenon that can influence a person's ability to make progress in treatment. We sought to understand how motivation is currently measured and utilized in aphasia rehabilitation by identifying treatment studies that (1) include measurement of motivation and (2) use motivation to predict treatment response. Method: A scoping review was conducted by systematically searching PubMed, CINAHL, EBSCO, Ovid MEDLINE, and APA PsycInfo using the following search terms: (measurement OR treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…GD patients are typically sensitive to placebo responses [ 19 , 144 ], although placebo or expectations effects in NiBS have also been documented in healthy individuals [ 145 , 146 , 147 ] and other clinical populations [ 148 , 149 , 150 , 151 ]. Previous authors hypothesized that the placebo response could be a component of the therapeutic response to NiBS [ 151 ] and—probably related to general motivation aspects—to favorable outcome treatments [ 152 , 153 , 154 ]. We believe that more randomized clinical trials are needed to disentangle whether the NiBS effect found in the present meta-analysis is trustworthy or primarily due to a placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…GD patients are typically sensitive to placebo responses [ 19 , 144 ], although placebo or expectations effects in NiBS have also been documented in healthy individuals [ 145 , 146 , 147 ] and other clinical populations [ 148 , 149 , 150 , 151 ]. Previous authors hypothesized that the placebo response could be a component of the therapeutic response to NiBS [ 151 ] and—probably related to general motivation aspects—to favorable outcome treatments [ 152 , 153 , 154 ]. We believe that more randomized clinical trials are needed to disentangle whether the NiBS effect found in the present meta-analysis is trustworthy or primarily due to a placebo effect.…”
Section: Discussionmentioning
confidence: 99%
“…Hunting Pompon and Mach (2022) provide a review of the literature related to resilience, coping, and adaptation and treatment outcomes for people with aphasia. Similarly, Weatherill et al (2022) conducted another scoping review focused on motivation and predicting treatment outcomes for people with aphasia. Finally, Engelhoven et al (2022) share the results of an analysis of the respondent burden and readability of various patient-reported outcome measures for people with aphasia.…”
mentioning
confidence: 99%